P136: What happens to bypassed trauma patients meeting Field Trauma Triage standards?. (May 2020) - Austin, M.; Sinclair, J.; Leduc, S.; Duncan, S.; Rouleau, J.; Price, P.; Evans, C.; Vaillancourt, C.
Abstract : Introduction: Prehospital field trauma triage (FTT) standards were reviewed and revised in 2014 based on the recommendations of the Centers for Disease Control and Prevention. The FTT standard allows a hospital bypass and direct transport, within 30 min, to a lead trauma hospital (LTH). Our objectives were to assess the impact of the newly introduced prehospital FTT standard and to describe the emergency department (ED) management and outcomes of patients that had bypassed closer hospitals. Methods: We conducted a 12-month multi-centred health record review of paramedic and ED records following the implementation of the 4 step FTT standard (step 1: vital signs and level of consciousness (physiologic), step 2: anatomical injury, step 3: mechanism and step 4: special considerations) in nine paramedic services across Eastern Ontario. We included adult trauma patients transported as urgent that met FTT standard, regardless of transport time. We developed and piloted a data collection tool and obtained consensus on all definitions. The primary outcome was the rate of appropriate triage to a LTH which was defined as: ISS ≥12, admitted to intensive care unit (ICU), non-orthopedic surgery, or death. We have reported descriptive statistics. Results: 570 patients were included: mean age 48.8, male 68.9%, falls 29.6%, motor vehicle collisions 20.2%, stab wounds 10.5%, transported to a LTH 76.5% (n = 436). 72.2% (n = 315) of patients transported to a LTH had bypassed a closer hospital and 126/306 (41.2%) of those were determined to be an appropriate triage to LTH (9 patients had missing outcomes). ED management included: CT head/cervical spine 69.9%, ultrasound 53.6%, xray 51.6%, intubation 15.0%, sedation 11.1%, tranexamic acid 9.8%, blood transfusion 8.2%, fracture reduction 6.9%, tube thoracostomy 5.9%. Outcomes included: ISS ≥ 12 32.7%, admitted to ICU 15.0%, non-orthopedic surgery 11.1%, death 8.8%. Others included: admission to hospital 57.5%, mean LOS 12.8 days, orthopedic surgery 16.3% and discharged from ED 37.3%. Conclusion: Despite a high number of admissions, the majority of trauma patients bypassed to a LTH were considered over-triaged, with a low number of ED procedures and non-orthopedic surgeries. Continued work is needed to appropriately identify patients requiring transport to a LTH.